2004
DOI: 10.1520/jfs2003031
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Implementation of the PowerPlex® 16 BIO System STR Multiplex for Forensic Casework

Abstract: The PowerPlex® 16 BIO multiplex short tandem repeat (STR) system contains the 13 CODIS loci (FGA, TPOX, D8S1179, vWA, D18S51, D21S11, TH01, D3S1358, CSF1PO, D16S539, D7S820, D13S317, and D5S818), plus two pentanucleotide repeat loci (Penta D and Penta E) and the sex-identifying locus, Amelogenin. The PowerPlex® 16 BIO System is optimized for use with the Hitachi FMBIO® gel imaging systems. A consortium of seven independent laboratories collaborated to perform the studies defined by the FBI standards for perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…(36) reported full detection of the minor contributor at the 3:1 and 1:3 ratios; however, the threshold setting was lower than that routinely applied to casework samples (50 rfu) and minor contributor alleles at the stutter position were excluded from analysis, which was not the case in the study reported here. Minor contributor alleles were above the peak threshold at many loci for both the 9:1 and 1:9 ratios as is also consistent with other reports (13,33,35,36). The dynamic coating polymer, pDuramide, was utilized for microchip coating in this experiment, which again indicated that this alternate coating procedure did not adversely impact μCAE device performance.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…(36) reported full detection of the minor contributor at the 3:1 and 1:3 ratios; however, the threshold setting was lower than that routinely applied to casework samples (50 rfu) and minor contributor alleles at the stutter position were excluded from analysis, which was not the case in the study reported here. Minor contributor alleles were above the peak threshold at many loci for both the 9:1 and 1:9 ratios as is also consistent with other reports (13,33,35,36). The dynamic coating polymer, pDuramide, was utilized for microchip coating in this experiment, which again indicated that this alternate coating procedure did not adversely impact μCAE device performance.…”
Section: Resultssupporting
confidence: 92%
“…The majority of minor contributor alleles were observed at the 3:1 and 1:3 ratios. However, at the 3:1 ratio, a 12 allele at D13S317 was below the threshold for reporting as were a 9 allele at TH01 and an 11 allele at Penta E. These findings are not unexpected and are consistent with previously reported mixture results using commercial detection platforms (33,35). All minor contributor alleles were reported in the Yeung et al.…”
Section: Resultssupporting
confidence: 90%
“…1). This case was initially analysed using 19 autosomal markers: D3S1358, vWA, D16S539, D2S1338, D8S1179, ACTBP2, D19S433, TH01, FIBRA, D21S11, D18S51, Penta E, D5S818, D13S317, D7S820, D16S539, CSF1PO, Penta D, and TPOX [1,9]. At the same time, we initiated X-chromosomal testing and investigated the Xq21 cluster described above together with 15 additional X-chromosomal markers reported earlier [2-4, 6, 7, 10, 12, 16].…”
Section: Casementioning
confidence: 99%
“…This multiplex was chosen for modification because of its readily available sequence information which is critical for primer design [19] and it has previously been validated for use on forensic casework evidence [20]. The ET 16-plex typing system was constructed first using the same primer concentrations in PowerPlex 16 (personal communication, Promega) followed by subsequent adjustments of primer concentrations by iteratively typing a single-source DNA sample, A-18.…”
Section: Et Labels Provide Increased Fluorescence Signalmentioning
confidence: 99%